Reliability assessment on interfacial failure of thermal barrier coatings - Guo, J.; Yang, L.; Zhou, Y.; He, L.; Zhu, W.; Cai, C.; Lu, Chunsheng (Springer, 2016)
© 2016 The Chinese Society of Theoretical and Applied Mechanics; Institute of Mechanics, Chinese Academy of Sciences and Springer-Verlag Berlin Heidelberg. Thermal barrier coatings (TBCs) usually exhibit an uncertain lifetime owing to their scattering mechanical properties and severe service conditions. To consider these uncertainties, a reliability assessment method is proposed based on failure probability analysis. First, a limit state equation is established to demarcate the boundary between failure and safe regions, and then the failure probability is calculated by the integration of a probability density function in the failure area according to the first- or second-order moment. It is shown that the parameters related to interfacial failure follow a Weibull distribution in two types of TBC. The interfacial failure of TBCs is significantly affected by the thermal mismatch of material properties and the temperature drop in service.